History of Islamic Banking and Finance - Islahi, Abdul Azim (Intellectual Discourse, 2018)
This paper aims to investigate the origins and evolution of Islamic Banking and Finance from the early days of Islam up to the formal establishment of Islamic banks in the sixties of the last century. It also sheds light on the banking practices in the later parts of Islamic history which is an almost unresearched area. It records the existence of interest free lending societies at the end of the 19th century and the situation preceding the development of modern Islamic banks in the second half of the twentieth century. The paper concludes that Islamic banking was an attempt to practice an aspect of economic life in an Islamic way and it first emerged in rural and agricultural economies and nothing to do with the petrodollar or oil boom of the Middle East as usually put forward.